Haptoglobin 2 Allele is Associated With Histologic Response to Vitamin E in Subjects With Nonalcoholic Steatohepatitis. Issue 10 (November 2019) - Banini, Bubu A.; Cazanave, Sophie C.; Yates, Katherine P.; Asgharpour, Amon; Vincent, Robert; Mirshahi, Faridoddin; Le, Peter; Contos, Melissa J.; Tonascia, James; Chalasani, Naga P.; Kowdley, Kris V.; McCullough, Arthur J.; et al.
Abstract : Background: Haptoglobin (Hp) genotype has been linked to oxidative stress and cardiovascular outcomes in response to vitamin E (VitE) among patients with diabetes mellitus. Its effect on histologic response to VitE in nonalcoholic steatohepatitis (NASH) is unknown. Goals: Our objective was to determine if Hp genotype associates with response to VitE in patients with NASH. Study: A post hoc analysis of 228 patients receiving VitE or placebo in 2 clinical trials was performed. Regression analysis was used to assess the effect of VitE versus placebo, by Hp genotype (1-1, 2-1, or 2-2), on histologic features and laboratory markers of nonalcoholic fatty liver disease, comparing baseline to end of treatment values. An interaction term was included in the regression models to assess differential treatment effect across Hp genotype. Results: Hp 2-2 patients treated with VitE versus placebo showed significant histologic improvement (51% vs. 20%; OR=4.2; P =0.006), resolution of steatohepatitis (44% vs. 12%; OR=6.2; P =0.009), decrease in nonalcoholic fatty liver disease Activity Score (NAS) (−2.2 vs. −0.6; P =0.001), and decrease in liver enzymes alanine aminotransferase, aspartate aminotransferase, alkaline phosphatase, and γ-glutamyl transpeptidase. Hp 2-1 patients on VitE versus placebo showed improved resolution of steatohepatitis, NAS and liver enzymes. Hp 1-1 patients showed no significant improvement in histology or liver enzymes. VitE had no effect on fibrosis stage in any group. Regression analysis showed incremental benefit of having Hp 2-2 or 2-1 versus 1-1 for all liver enzyme. Conclusions: Hp 2 allele is associated with greater histologic and biological improvement in NASH with VitE treatment compared with the Hp 1 allele. Abstract : Supplemental Digital Content is available in the text.